Accuracy and patient‐centered outcome variables in guided implant surgery: a RCT comparing immediate with delayed loading. Issue 4 (28th March 2015) - Vercruyssen, Marjolein; Cox, Catherine; Naert, Ignace; Jacobs, Reinhilde; Teughels, Wim; Quirynen, Marc
Abstract: Aim: To assess the accuracy and patient‐centered outcome of a novel guided surgery system for placing implants in an edentulous maxilla. Material and methods: Fifteen consecutive patients with sufficient bone to place six implants in the maxilla were randomly assigned to the immediate loading (with delivery of the final prosthesis within 24 h) or the delayed loading treatment group. Accuracy was assessed by matching the planning CT with a postoperative CBCT. Patient‐centered outcome measures were the Dutch version of the McGill Pain Questionnaire (MPQ‐DLV), the health‐related quality of life instrument (HRQOL), visual analog scales (VAS), the duration of the procedure, and the analgesic doses taken each day. Results: A mean deviation was found at the entry point of 0.9 mm (range: 0.1–4.5, median 0.8) and of 1.2 mm (range: 0.2–4.9, median 1.1) at the apex, and an angular deviation of 2.7° (range: 0.0–6.6°, median 2.3) was observed. The mean vertical deviation was 0.5 mm (range: 0.0–3.2, median 0.4), and in a horizontal direction, this was 0.7 mm (range: 0.1–3.1, median 0.6). The mean deviation in mesio‐distal direction was 0.5 mm (range: 0.0–2.3, median 0.4) and in bucco‐lingual direction 0.5 mm ± 0.4 (range: 0.0–2.2, median 0.3). No statistical differences could be shown between treatment groups on pain response (MPQ‐DLV), treatment perception (VAS), number or kind of pain killers, or for the HRQOLI instrument. Conclusion: The accuracy of a novel CT‐based guide is comparable to the accuracy data of other systems. Within the limitations of this study, no difference could be found in patient‐centered outcome variables after immediate or delayed loading.